PREPARING FUTURE PHYSICAL EDUCATORS FOR INCLUSION: CHANGING THE PHYSICAL EDUCATION TEACHER TRAINING PROGRAM - BLOCK, Martin E.; KWON, Eun Hye; HEALY, Sean (UNESP, 2016)
Students with disabilities around the world are leaving special schools and special classes and are receiving their education in general education schools. In addition to attending general education classes, these students with disabilities are attending general physical education classes. Unfortunately, research has clearly demonstrated that physical educators do not feel prepared to include students with disabilities into their general physical education classes. Such findings are not surprising given that the typical physical education teacher education program in the United States only requires one course in adapted physical education, and in many countries around the world not even one adapted physical education course is required. However, many physical education teacher education programs do not have the space to add more adapted physical education classes, and other universities do not have professors with specialized knowledge to teach adapted physical education. What can be done to better prepare future and current physical educators? Online education is a relatively new method for delivering information about disability in general and more specifically how to include students with disabilities into general physical activities. The purpose of this paper is to introduce online education and present preliminary research that supports the use of online training with physical educators.